Negotiating urban identities: race, class, and gender - Ehland, Christoph,Fischer, Pascal (Brill Rodopi, 2018)
Introduction 1 / Christoph Ehland and Pascal Fischer – Introduction 11 / Christoph Ehland and Pascal Fischer Part 1. Race and Ethnicity 1 Black Citizens - British Spaces. Struggles in the 1970s and 1980s and Cinematic Representations / Ingrid von Rosenberg 2 Resisting Topographies: Immigration, Space and the City in Contemporary British Film / Ralf Schneider 3 Heterotopias as Spaces of Resistance in Salman Rushdie's Midnight's Children (1981) / Katrin Roder 4 Changing Uses of the City in Contemporary Black British Novels / Merle Tonnies and Anna Lienen Part 2. Social Class. 5
Includes bibliographical references and index
Keywords: English literature; City and town life in literature; Identity (Psychology) in literature; Marginality; Social; in literature; City and town life in motion pictures; Identity (Psychology) in motion pictures; Marginality; Social; in motion pictures